DINAMIKA PERILAKU MANAJEMEN LIKUIDITAS PERBANKAN INDONESIA - Putra, Adrie (Jurnal Ekonomi : Journal of Economic, 2017)
The purpose of this research is to create a model of detecting Indonesian banking liquidity by linking internal and external factors of banking liquidity itself. The research variables include financial economic variables and banking plus banking characteristics. The focus of research research is directed to the development of a model to determine the determinants of banking operations in carrying out its main function as an intermediary institution in the community based on Dynamic Panel Data GMM Arelano Bond. The data used is data from 2002 to 2015. The process of data processing starts from the graphicization of the main indicators of banking intermediation (loan to deposit ratio). Then an inferential analysis of econometrics based on the dynamic model of banking behavior. In this way will be able to obtain information determinant variable which becomes the key variable to detect liquidity early. The primacy of the research is that the model that will be produced can (1) be applied and able to provide very useful information in controlling bank liquidity policy (2) become a reference for monetary policy makers, especially BI (Bank Indonesia) and OJK (Indonesian Financial Services Authority) to stimulate the development of financial markets. (3) this model can also be used as a reference for the financial and banking world in order to improve the mobility of public funds, and (4) as reference materials for further research. This model can be used as a means of dissemination and publication for observers of finance and banking in understanding the condition of money market / bank and capital market. The implications of this research will produce targets and findings in the form of (1) Construction of the dynamics model of the behavior of Indonesian banking liquidity management. (2) The model of policy and strategy in creating added value for domestic industries and economy as a positive driving factor for the growth and development of national economy; (3) Dissemination of research results at the National Business Seminar organized by the Association of Management Professors or State and Private Universities in IndonesiaÂ Keywords: liquidity, characteristic, performance